10-YEARS ANALYSIS OF CRYOBAG FRACTURE IN A LARGE INVENTORY OF CELLULAR THERAPY PRODUCTS: RATES AND RISK FACTORS - AR Belisário; LT Mendonça; RK Andrade; MC Martins; LA Costa; KL Prata (Hematology, Transfusion and Cell Therapy)
Aim: Cryobags are crucial for the freezing, storage and transport of cellular therapy products. Despite their widespread use and importance, cryobags are vulnerable to damage, and fractures can significantly impact both patient outcomes and the operational efficiency of cellular therapy facilities. To date, there have been no reported studies on Peripheral Blood Stem Cell (PBSC) bag fractures. This study aimed to investigate the incidence and determinants of cryobag fractures within a large inventory of cellular therapy products in Brazil. Methods: This retrospective cohort study included cryobags from individuals referred for hematopoietic stem cell transplantation or immunotherapy. Cryopreservation was performed at a single processing facility between 2015‒2024, with clinical care provided at nine transplant centers. The products were centrifuged, and plasma was removed to adjust the buffy coat to achieve the final Total Nucleated Cell (TNC) concentration of ≤7.5×108 cells/mL after adding the cryopreservation solution. Cryobags (CryoStore CS500N, OriGen Biomedical, Austin, TX, USA) were frozen at an uncontrolled rate in a -80°C mechanical freezer and stored in a vapor phase storage tank. The frozen cryobags underwent macroscopic evaluation in the vapor phase through visual inspection to check for fractures and leaks. Records were reviewed to gather information on covariates and outcomes. Results: During the study period, 2,078 PBSC collections were performed for 1,637 patients (911 [55.7%] male) with ages ranging from 1- to 75-years. Multiple myeloma was the most common diagnosis (59.8%), followed by lymphoma (27.9%). Among the 2,078 products collected, 514 (24.7%) were processed from components collected in two consecutive apheresis procedures, and 1,564 (75.3%) were processed after a single apheresis procedure, resulting in 1,821 cryopreservation procedures. Each cryopreservation procedure resulted in one to seven cryobags being frozen, totaling 4,144 cryobags studied. Out of these, 15 (0.4%) experienced fractures. Of the 15 fractures, 13 (86.7%) were detected during macroscopic evaluation in the processing facility, and two (13.3%) occurred after the cryobags were released to the transplant center. The incidence rate of cryobag fractures was 0.41 (95% CI 0.23–0.66) per 100 bag-years. The cumulative incidence of fractures after 3.16-years of storage was 1% (95% CI 0.7%–1.3%). Multivariate analysis identified two independent predictors of cryobag fracture: the initial TNC count (OR = 1.002, 95% CI 1.001–1.003; p < 0.001) and hematocrit (OR = 0.55, 95% CI 0.34–0.90; p = 0.018). When compared to products with an initial TNC ≤ 10×108 cells/mL, those with TNC > 10×108 cells/mL had 10.8 times higher odds (95% CI 3.3–35.9; p < 0.001) of triggering a cryobag fracture. Discussion: This study provides critical insights into cryobag fractures incidence and determinants. Our findings highlight two key predictors of cryobag fractures. Elevated TNC concentrations were associated with an increased risk of fractures due to heightened mechanical stress and potential ice crystal formation. Conversely, higher hematocrit levels were associated with a decreased risk of fractures, likely due to enhanced cryoprotectant effectiveness and increased stability within the cryobag. These insights underscore the importance of monitoring and optimizing both TNC and hematocrit levels during the preparation of cellular therapy products. Conclusion: This study revealed a low cryobag fracture rate of 0.4 per 100 bag-years. Higher total nucleated cell counts increased fracture risk, while higher hematocrit levels reduced it. Optimizing these factors in cryopreservation protocols could enhance the safety and reliability of cellular therapy products.